2023
DOI: 10.9734/jamb/2023/v23i10763
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacteriophage against Drug-resistant Staphylococcus aureus

Sajib Kumar Saha,
Md. Ashiqur Rahman,
Md. Sultan Mahmud
et al.

Abstract: Staphylococcus aureus is one of the most successful pathogens due to its vast arsenal of virulence factors, including anchor proteins, secreted toxins and enzymes, polysaccharides, and immune system modulators. Bacteriophages are viruses that specifically target and infect bacterial cells. Bacteriophage is studied widely to improve the safety of foods and prevent food borne diseases of bacterial etiology, as well as to reduce the use of antibiotics in livestock. Besides, therapeutic applications of bacteriopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…A similar rising trend of enterococcal resistance to various antibiotics was noted in another Indian study by Shinde in a tertiary care hospital in Mumbai [24] . One study concluded that Enterococci have emerged from being harmless commensals to versatile lethal pathogens.…”
Section: Discussionsupporting
confidence: 79%
“…A similar rising trend of enterococcal resistance to various antibiotics was noted in another Indian study by Shinde in a tertiary care hospital in Mumbai [24] . One study concluded that Enterococci have emerged from being harmless commensals to versatile lethal pathogens.…”
Section: Discussionsupporting
confidence: 79%